Response of guava (Psidium guajava L.) genotypes to air layering under sub-humid southern Rajasthan (Current Horticulture, 2024)
The evaluation of guava genotypes (Psidium guajava L.) for air layering under sub-humid conditions in the southern plains of  Rajasthan was conducted from 5th to 15th July 2015-16. The following genotypes were used: L-49, Allahabad Safeda, Lalit, Red  Fleshed, Pant Prabhat, Safed Jam, Arka Amulya, Arka Mridula, MPUAT S-1, MPUAT S-2, Shweta, Burfkhan, Sarbati, RCGH-1,  and One-Kg. Among the genotypes, Lalit exhibited the highest early root initiation, percentage of rooted air layers, survival  percentage, and vigor index. The number of secondary roots was highest in L-49, and the root-to-shoot ratio was highest in  Shweta. One-Kg showed a poor response to rooting.
Keywords: Chinese layering performance; Sub-humid condition; Red and white fleshed genotypes; Air layering